2022
DOI: 10.1002/adem.202101367
|View full text |Cite
|
Sign up to set email alerts
|

High‐Strength Composites Based on 3D Printed Porous Scaffolds Infused with a Bioresorbable Mineral–Organic Bone Adhesive

Abstract: Bioresorbable bone adhesives are attractive materials for applications where bone repair, regeneration, or reconstruction is involved. They can potentially augment or replace metal fixation while allowing to avoid follow‐up procedures upon bone healing. Combining such bone adhesives with other clinically relevant materials could significantly improve the mechanical and biological properties of the resulting composite due to the strong adhesive interactions between the adhesive and the material. Herein, an effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…To the best of the authors' knowledge, this is the first work dealing with the production and comparison of two different TPMS-type scaffolds using the commercial Dental LT clear resin, which is commonly used for medical purposes. Looking at the previous literature, only one study was found, where Karillova et al [33] produced gyroid scaffolds using Dental LT clear resin by stereolithography and compared them with analogous structures obtained by using different materials and additive manufacturing techniques. However, that study was not addressed to assess the mechanical properties of the specific TMPS geometry, but to develop a strategy to create biomedically relevant composite scaffolds using a bioceramic-based bone adhesive.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of the authors' knowledge, this is the first work dealing with the production and comparison of two different TPMS-type scaffolds using the commercial Dental LT clear resin, which is commonly used for medical purposes. Looking at the previous literature, only one study was found, where Karillova et al [33] produced gyroid scaffolds using Dental LT clear resin by stereolithography and compared them with analogous structures obtained by using different materials and additive manufacturing techniques. However, that study was not addressed to assess the mechanical properties of the specific TMPS geometry, but to develop a strategy to create biomedically relevant composite scaffolds using a bioceramic-based bone adhesive.…”
Section: Introductionmentioning
confidence: 99%
“…With advances in tissue and biomedical engineering, there is a growing demand for functional structures. Several methods, such as electrospinning ( Adadi et al, 2020 ), microfluidics ( Navaei-Nigjeh et al, 2023 ), and (bio)printing ( Kirillova et al, 2022 ), have been used to fabricate structures for tissue scaffolds, temporary or permanent implants, sensors, and minimally invasive devices. While improvements in some properties of these structures, such as biocompatibility and mechanical properties, fabricating sensors, scaffolds, and tissues that meet the needs of complex biological can laborious and methodologically difficult.…”
Section: Introductionmentioning
confidence: 99%